52 TOPICAL THERMAL THERAPY IN THE MANAGEMENT OF ELDERLY PATIENTS WITH HEART FAILURE. Issue 1 (1st January 2007) - Weber, A. A.; Brennan, S.; Lonergan-Thomas, H.; Cianci, P.; Feldman, C.; Silver, M. A.
Abstract : Purpose: Elderly patients with heart failure suffer from reduced systemic perfusion and increased vascular resistance (SVR). Pharmacologic vasodilators can improve perfusion and symptomatic failure and some can improve survival. There is an emerging interest in finding inexpensive, nonpharmacologic means to induce vasodilation. This includes thermal baths, saunas, and topical thermal therapy (TTT). However, heat therapy in the elderly can be associated with tachycardia, hypotension, and ventricular arrhythmias. Herein, we undertook this preliminary study with TTT to address its hemodynamic effects and safety in elderly patients with heart failure. Methods and Results: We enrolled 12 outpatients (5 M, 7 F; 77 ± 2 years) with chronic failure (NYHA class II and III) and reduced ejection fraction (< 35%) secondary to ischemic or dilated (idiopathic) cardiomyopathy and stable medical therapy (angiotensin-converting enzyme inhibitor, beta-blocker, and diuretic). Patients were randomized to receive 1 hour of upper ( n = 7) or lower torso ( n = 5) TTT (65°C) based on their even or odd year of birth, respectively. In a reclining chair, upper torso TTT was applied with a CardioVest® that covered the anterior chest and upper shoulders; CardioLegs® covered the full length of the lower extremities from hips to ankles. At baseline, every 15 minutes of TTT, and 60 minutes post-TTT, we monitored heart rate (HR) and rhythm by ECG; systolic, diastolic, and mean (MAP) arterial pressures, cardiac index (CI), calculated SVR, and thoracic fluid content (TFC) by impedance cardiography as well as small (SAC) and large arterial (LAC) compliances. We found (mean ± SEM) no statistical difference from baseline in HR (80 ± 2 bpm) or rhythm, MAP (73 ± 7 mm Hg), CI (2.42 ± 0.1 L/min/m 2 ), SVR (1, 393 ± 125 dynes·s·cm −5 ), or TFC (29 ± 2 kOhm) during or at 60 minutes after upper torso TTT. Similarly, these parameters were unchanged during and 1 hours after lower torso TTT. At 1 week of follow-up, there was a trend to improved LAC and SAC. Conclusions: TTT can be safely applied without tachycardia, hypotension, or arrhythmias to the upper or lower torso in elderly patients with heart failure. TTT represents a simple, easily accessible, and inexpensive nonpharmacologic strategy that could prove efficacious in the home management of elderly patients with heart failure, who are already overburdened with medications. Long-term responses to chronic treatment with TTT now need to be examined.